Forma urbana da cidade tradicional e da cidade de contemporânea em são Luís - Maranhão: análise das áreas verdes públicas e da urbanidade do Centro Histórico (Praça João Lisboa) e em uma nova centralidade (Praça do Viva do Conj. Hab. da Cidade Operária) - Silva, Patricia Rachel Pinto (2018)
Modern urbanism has brought a clear break with traditional urbanism in formal terms, in terms of scale and ideology. The various types of urbanity and appropriation of public spaces are also related to urban forms, that is, to the way the cities are drawn. In general terms, public spaces, especially public green areas, would have an integrative and aesthetic function in the city, since they are spaces that help the city to fulfill its social function, with spaces of leisure and democratic expression, besides being a morphological element which promotes well-being and is associated with quality of life. The public green areas are places that express the identity of the communities, and the place where the right to the city can be exercised, being possible to make a social reading through these spaces. In the modern city and in the contemporary city are seen the practices of urbanism subjugated to the power of the capital, demonstrating how the urban landscape is being produced and reproduced having its public green areas being depredated in function of the maximum use of the ground. The main debate of this dissertation is how modern urbanism impacted on the urban form of the city of São Luís and what changes in the configuration of the public green areas. It starts from the hypothesis that the production of the urban space of São Luís, inspired by the modernist ideas, was an instrument of social ordering and configures the territory according to the interests of capital. And to retake urbanity in the analyzed neighborhoods the proposition is the use of the principles of integrated conservation (CI) adopted in Europe to recover degraded areas since the 1970s